A Diels–Alder probe for discovery of natural products containing furan moieties - Eggly, Alyssa S.; Otgontseren, Namuunzul; Roberts, Carson B.; Alwali, Amir Y.; Hennigan, Haylie E.; Parkinson, Elizabeth I. (Beilstein Journal of Organic Chemistry, 2024)
Natural products (NPs) are fantastic sources of inspiration for novel pharmaceuticals, oftentimes showing unique bioactivity against interesting targets. Specifically, NPs containing furan moieties show activity against a variety of diseases including fungal infections, and cancers. However, it is challenging to discover and isolate these small molecules from cell supernatant. The work described herein showcases the development of a molecular probe that can covalently modify furan moieties via a [4 + 2] Diels–Alder cycloaddition, making them easily identifiable on liquid chromatography–mass spectrometry (LC–MS). The molecular probe, which undergoes this reaction with a variety of furans, was designed with both a UV-tag and a mass tag to enable easy identification. The probe has been tested with a variety of purified furans, including natural products, methylenomycin furan (MMF) hormones, and MMF derivatives. Moreover, the molecular probe has been tested in crude supernatants of various Streptomyces strains and enables identification of MMFs.
Keywords: Diels–Alder reaction; furans; methylenomycin furan hormones; natural products; reactivity-based probes